Analisis Intention To Use Mobile Banking Pada Bank Mayora - Novia Sarah Christyana BR Siahaan; Irzameingindra P Radjamin; mintarti ariani (Journal of Economics Development Issues, 2022)
Service Quality, System Quality, and Trust on Intention to Use of Mayora Bank’s Mobile Banking in Surabaya. To calculate the sample, the Slovin formula was used. Questionnaires have been distributed among 100 customers of Bank Mayora Surabaya. The data has been analyzed using SPSS 22.0 in two segments. First, the questionnaires were tested in terms of Reliability and Validity using 30 data from 100 data samples. Then, the data were tested in a t-test, f-test, and did the classic assumption test. The result of this study showed that there was a positive impact between System Quality and Trust with the Intention to Use Mobile Banking of Mayora Bank in Surabaya. Moreover, this study found that there were negative impacts between Information and service Quality with the Intention to Use of Mayora Bank’s Mobile Banking. ABSTRAKKualitas Layanan, Kualitas Sistem, dan Kepercayaan atas Niat Penggunaan Mobile Banking Bank Mayora di Surabaya. Untuk menghitung sampel, digunakan rumus Slovin. Kuesioner ini telah disalurkan kepada 100 nasabah Bank Mayora Surabaya. Data telah dianalisis menggunakan SPSS 22.0 dalam dua segmen. Pertama, kuesioner diuji dalam hal Reliabilitas dan Validitas menggunakan 30 data dari 100 sampel data. Kemudian, data diuji dalam t-test, f-test dan melakukan tes asumsi klasik. Hasil penelitian ini menunjukkan bahwa terdapat dampak positif antara kualitas sistem dan Kepercayaan dengan niat menggunakan mobile banking Bank Mayora di Surabaya. Selain itu, penelitian ini menemukan bahwa ada dampak negatif antara Informasi dan Kualitas layanan dengan niat untuk menggunakan mobile banking Bank Mayora.